Gerakan Nasional Literasi Digital: Sinergi Pemerintah, Komunitas, dan Media dalam Menghadapi Tantangan Era Digital di Bangka Belitung - Utami, Atikah Dewi; Harista, Eva (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
The National Digital Literacy Movement (GNLD) is one of Indonesia’s strategic initiatives to strengthen citizens’ capacity in facing digital era challenges. Digital literacy encompasses not only technical skills but also ethics, safety, digital culture, and critical thinking in managing information. This study aims to analyze GNLD implementation from the perspectives of development communication and multi-stakeholder collaboration, focusing on the Bangka Belitung Islands Province (Bangka Belitung), which ranked second nationally in Indonesia’s Digital Society Index (IMDI) 2025 with a score of 52.15. Using a literature review approach, this research examines the roles of government, local communities, media, and educational institutions in promoting inclusive and sustainable digital literacy development. The findings reveal that Bangka Belitung’s success is rooted in participatory development communication, strong inter-stakeholder synergy, and effective public policies that enhance citizens’ digital awareness and competence. Moreover, multi-stakeholder collaboration has been a key factor in accelerating digital transformation across the archipelago region. This study provides theoretical contributions to development communication discourse and practical insights for digital literacy policy implementation in other regions of Indonesia.